2022
DOI: 10.1016/j.apsb.2021.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Bioresponsive immune-booster-based prodrug nanogel for cancer immunotherapy

Abstract: The combination of chemotherapy and immunotherapy motivates a potent immune system by triggering immunogenic cell death (ICD), showing great potential in inhibiting tumor growth and improving the immunosuppressive tumor microenvironment (ITM). However, the therapeutic effectiveness has been restricted by inferior drug bioavailability. Herein, we reported a universal bioresponsive doxorubicin (DOX)-based nanogel to achieve tumor-specific co-delivery of drugs. DOX-based mannose nanogels (DM NGs) was designed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 62 publications
0
41
0
Order By: Relevance
“…In recent years, studies have shown that Graphene (Deb et al., 2018 ), gold nanocages (Zhang et al., 2018b ), hydrogels (Ren et al., 2019 ; Wang et al., 2019b ; Abedi et al., 2021 ), prodrug nanogel (Ma et al., 2022 ), microspheres (Liu et al., 2017 ; Xu et al., 2021 ) and nanoclusters (He et al., 2020 ) can also be used for the co-delivery of natural active ingredients of and chemotherapy drugs. A summary of the researches of other nanocarriers used to co-deliver chemotherapy drugs and natural active ingredients is shown in Table 9 .…”
Section: Types and Characteristics Of Ndcdsmentioning
confidence: 99%
“…In recent years, studies have shown that Graphene (Deb et al., 2018 ), gold nanocages (Zhang et al., 2018b ), hydrogels (Ren et al., 2019 ; Wang et al., 2019b ; Abedi et al., 2021 ), prodrug nanogel (Ma et al., 2022 ), microspheres (Liu et al., 2017 ; Xu et al., 2021 ) and nanoclusters (He et al., 2020 ) can also be used for the co-delivery of natural active ingredients of and chemotherapy drugs. A summary of the researches of other nanocarriers used to co-deliver chemotherapy drugs and natural active ingredients is shown in Table 9 .…”
Section: Types and Characteristics Of Ndcdsmentioning
confidence: 99%
“…7b). 114 After entering tumour cells, the GSH-responsive cross-linker would decompose in response to excessive GSH, releasing DOX and MAN. Meanwhile, DOX induced tumour ICD while MAN enhanced the sensitivity of tumour cells to chemotherapy, and the synergistic effect of the two drugs enhanced the infiltration of immune cells and restored exhausted TIM3 + PD-1 + T cells, and ultimately the survival time of mice was significantly prolonged.…”
Section: Nanogels For Immunomodulatory Therapeuticsmentioning
confidence: 99%
“…DOX and mannose were co‐loaded to perform a combined chemo/immunotherapy. Specifically, DOX‐induced chemotherapy could cause tumor immunogenic cell death (ICD), manifesting the release of high‐mobility group box 1 (HMGB1) and the expose of calreticulin (CRT) on the cell membrane, resulting in an antitumor immune response to maximize the immune‐regulation effects from mannose (Ma, Yang, et al, 2021). Meanwhile, FIL was utilized to track the in vivo biodistribution and pharmacokinetics of the NGs.…”
Section: Nanotheranostics Based On Nir Light As Triggermentioning
confidence: 99%